(untitled) (Neo Science Peer Reviewed Journal, 2025)
Peptic ulcer disease (PUD) of the stomach and duodenum remains a significant global health problem despite substantial advances in gastroenterology over recent decades, largely due to its high prevalence, recurrent nature, and potential for severe complications such as bleeding, perforation, and gastric outlet obstruction. The present scientific article aims to provide a comprehensive and evidence-based analysis of modern therapeutic approaches to gastric and duodenal peptic ulcer disease, with particular emphasis on pathogenetic treatment strategies, eradication of Helicobacter pylori, acid-suppressive therapy, and emerging pharmacological and endoscopic interventions. Contemporary concepts of ulcerogenesis are reviewed, highlighting the central role of acid-peptic aggression, mucosal defense mechanisms, infectious factors, and drug-induced mucosal injury, particularly non-steroidal anti-inflammatory drugs. Special attention is given to the evolution of treatment paradigms from symptom-oriented management to targeted etiological therapy guided by international consensus documents and clinical practice guidelines. The article synthesizes current data from randomized controlled trials, meta-analyses, and authoritative international recommendations, including the Maastricht VI/Florence Consensus Report, to evaluate the efficacy and safety of proton pump inhibitors, potassium-competitive acid blockers, antibiotic combinations, and adjunctive mucosal protective agents. In addition, modern diagnostic and therapeutic algorithms, challenges related to antibiotic resistance, and prospects for personalized treatment approaches are critically discussed. This work is intended to serve as a scientific and practical resource for clinicians, researchers, and healthcare professionals involved in the management of peptic ulcer disease in contemporary clinical practice.